Learning mode, university students’ mental health, and acculturative stress: A cross-sectional study of Chinese international students in Melbourne, Australia - Zuo, Peixin; Gowing, Ann; De Silva, Anurika; Minas, Harry (Journal of International Students, 2026)
This study examines the association between the learning mode and the mental health of Chinese international students (CIS) in Australia and the potential mediating role of acculturative stress. One hundred and twenty-two CIS were recruited through an online survey and assigned to either the in-person or hybrid learning group according to their mode of learning. Depression, anxiety, and acculturative stress were assessed using the Patient Health Questionnaire-9 (PHQ-9), the General Anxiety Disorder-7 (GAD-7), and the Acculturative Stress Scale for Chinese College Students (ASSCS), respectively. The results indicated that compared with participation in in-person learning, participation in hybrid learning was associated with higher levels of self-reported symptoms of depression and anxiety. Acculturative stress was found to play a mediating role in this association.